(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Here we propose a framework that enables clients to get moment direction on their medical problems through an astute social intelligent health care system online. The framework is bolstered with different symptoms and the disease or illness associated with those systems. Also the system allows user to share their symptoms and issues. Data Mining as a field of research has already well proven capabilities of identifying hidden patterns, analysis and knowledge applied on different research domains, now gaining popularity day by day among researchers and scientist towards generating novel and deep insights of these large biomedical datasets also. Uncovering new biomedical and healthcare related knowledge to support clinical decision making, is another dimension of data mining. Through massive literature survey, it is found that early disease prediction is the most demanded area of research in health care sector.